Stress Signaling JNK2 Crosstalk With CaMKII Underlies Enhanced Atrial Arrhythmogenesis. Issue 6 (16th March 2018) - Yan, Jiajie; Zhao, Weiwei; Thomson, Justin K.; Gao, Xianlong; DeMarco, Dominic M.; Carrillo, Elena; Chen, Biyi; Wu, Xiaomin; Ginsburg, Kenneth S.; Bakhos, Mamdouh; Bers, Donald M.; Anderson, Mark E.; et al.
Abstract : Rationale: : Atrial fibrillation (AF) is the most common arrhythmia, and advanced age is an inevitable and predominant AF risk factor. However, the mechanisms that couple aging and AF propensity remain unclear, making targeted therapeutic interventions unattainable. Objective: : To explore the functional role of an important stress response JNK (c-Jun N-terminal kinase) in sarcoplasmic reticulum Ca 2+ handling and consequently Ca 2+ -mediated atrial arrhythmias. Methods and Results: : We used a series of cutting-edge electrophysiological and molecular techniques, exploited the power of transgenic mouse models to detail the molecular mechanism, and verified its clinical applicability in parallel studies on donor human hearts. We discovered that significantly increased activity of the stress response kinase JNK2 (JNK isoform 2) in the aged atria is involved in arrhythmic remodeling. The JNK-driven atrial proarrhythmic mechanism is supported by a pathway linking JNK, CaMKII (Ca 2+ /calmodulin-dependent kinase II), and sarcoplasmic reticulum Ca 2+ release RyR2 (ryanodine receptor) channels. JNK2 activates CaMKII, a critical proarrhythmic molecule in cardiac muscle. In turn, activated CaMKII upregulates diastolic sarcoplasmic reticulum Ca 2+ leak mediated by RyR2 channels. This leads to aberrant intracellular Ca 2+ waves and enhanced AF propensity. In contrast, this mechanism is absent in young atria. In JNK challenged animal models, this is eliminated by JNK2 ablation or CaMKII inhibition. Conclusions: : We have identified JNK2-driven CaMKII activation as a novel mode of kinase crosstalk and a causal factor in atrial arrhythmic remodeling, making JNK2 a compelling new therapeutic target for AF prevention and treatment. Abstract : Supplemental Digital Content is available in the text.